Multiple roles of neuronal extracellular vesicles in neurological disorders - Jiao, Zhigang; He, Zhengyi; Liu, Nanhai; Lai, Yanwei; Zhong, Tianyu (Frontiers in Cellular Neuroscience, 2022)
Neuropathy is a growing public health problem among aging, adolescent, and sporter population, and the number of individuals at risk of neuropathy is growing, these risks including aging, violence, and force. Incomplete understanding of the pathways underlying neuron aging and damage, as well as insufficient delivery of evidence-based treatment to patients with neuropathy are the part of reason on neuropathy that is still not completely cured or inhibits the progression of disease. The extracellular vesicles (EVs) shuttle is an important pathway in disease progression. Previous studies focused on the EVs of cells such as astrocyte or microglia that support and protect neurons. This review aims to address the role of neuronal EVs by delineating updated mechanisms of neuronal damage and summarizing recent findings on the function of neuronal EVs. Challenges and obstacles in isolating and analysis for neuronal EVs are discussed, with an emphasis on neuron as research object and modification of EVs on translational medicine.